2017
DOI: 10.1016/j.ntt.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of isoflurane-induced developmental neurotoxicity

Abstract: Introduction Neurotoxicity induced by early developmental exposure to volatile anesthetics is a characteristic of organisms across a wide range of species, extending from the nematode C. elegans to mammals. Prevention of anesthetic-induced neurotoxicity (AIN) will rely upon an understanding of its underlying mechanisms. However, no forward genetic screens have been undertaken to identify the critical pathways affected in AIN. By characterizing such pathways, we may identify mechanisms to eliminate isoflurane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 82 publications
4
17
0
Order By: Relevance
“…This is in contrast to previous behavioral measurements in which daf-2 null mutants did not display changes in chemotaxis index upon developmental anesthetic exposure. 29 Thus, apoptotic cell death as well as insulin signaling, both of which have previously been implicated in the neurotoxic effects of anesthetic, appear to be independent of the subtle alterations in neuronal function measured here. Reconciliation of this discrepancy likely lies in the relative complexity of C. elegans chemotaxis, the efficient undertaking of which is dependent upon various behaviors that contribute to locomotive stochasticity and also upon neurophysiological processes, such as chemosensation.…”
Section: Isoflurane: Persistent Changes In Neuron Dynamicssupporting
confidence: 50%
See 3 more Smart Citations
“…This is in contrast to previous behavioral measurements in which daf-2 null mutants did not display changes in chemotaxis index upon developmental anesthetic exposure. 29 Thus, apoptotic cell death as well as insulin signaling, both of which have previously been implicated in the neurotoxic effects of anesthetic, appear to be independent of the subtle alterations in neuronal function measured here. Reconciliation of this discrepancy likely lies in the relative complexity of C. elegans chemotaxis, the efficient undertaking of which is dependent upon various behaviors that contribute to locomotive stochasticity and also upon neurophysiological processes, such as chemosensation.…”
Section: Isoflurane: Persistent Changes In Neuron Dynamicssupporting
confidence: 50%
“…In recent behavioral genetics studies, Morgan, Sedensky, and colleagues 10,29 identified molecular modulators of the chemotaxis deficits that follow developmental anesthetic exposure in C. elegans. Key among these are genes within the apoptosis cell death pathway, the daf-2-dependent stress-response pathway, and the mechanistic Target of Rapamycin (mTOR).…”
Section: Multineuron Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Na and co-workers found that rapamycin treatment prevented the loss of chemotaxis that results from developmental exposure of C. elegans to isoflurane. Based on this data and the results of a forward genetics screen that identified endoplasmic reticulum stress pathways as a target in anesthetic-induced neurotoxicity, that isoflurane acts on mitochondria to create reactive oxygen species that in turn activate the mTOR pathway [ 30 ]. In our recently published manuscript, we described a study in a mouse model of developmental anesthetic neurotoxicity which revealed that anesthetic effects on mTOR signaling profoundly disrupted development of newborn dentate gyrus granule cells in the hippocampus.…”
Section: Mtor As a Target In Developmental Anesthetic Neurotoxicitymentioning
confidence: 99%